KARAKTERISASI TABLET EFFERVESCENT SARANG SEMUT (Myrmecodia tuberosa) – ROSELLA (Hibiscus sabdarisffa L.) BERBAHAN PENGISI MALTODEKSTRIN DAN DEKSTRIN - Irma Purwati; Sih Yuwanti; Puspita Sari (JURNAL AGROTEKNOLOGI, 2016)
The aims of this study were to determine the characteristics of effervescent tablet using anthill-rosella ratio with maltodextrin and dextrin as a filler, and to determine the treatment with the best characteristics of effervescent tablets anthil and rosella. Anthill - rosella ratio which used in this study were 100: 0, 90:10, 80:20, 70:30, and 60:40. The results showed that anthill - rosella ratio, maltodextrin and dextrin as fillers significantly affect the characteristics of effervescent tablets. The as increated the rosella concertration, the lightness, total polyphenols and antioxidant activity were decreased, and chroma, hue, moisture content, hygroscopicity, solubility time and total anthocyanins were increased. The use of maltodextrin as filler in effervescent tablets anthill - rosella produced higher polyphenols, anthocyanins and antioxidants activity than dextrin. The best treatment of anthill - rosella ratio was 70:30 with maltodextrin as filler. That effervescent tablet had water content of 12.32%, hygroscopicity of 4,12%, soluble time of 73,15 seconds, Lighness (L) of 70,54, Chroma (C) of 20,85, Hue (H) of 89,58 (Yellow Red), polyphenol content of 5,9 mg GAE /g, anthocyanin content of 0,38 mg/g and the antioxidant activity of 53,97%.Keywords: effervescent tablet, anthill, rosella, filler, maltodextrin, dextrin